2020
DOI: 10.2147/dmso.s250133
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Blood Glucose Within 24 Hours After Intensive Care Unit Admission and Prognosis: A Retrospective Cohort Study</p>

Abstract: The aim of this study was to evaluate the association between blood glucose within 24 hours after intensive care unit (ICU) admission and prognosis. Patients and Methods: A retrospective cohort study was conducted using data from a large critical care database. Patients who had a length of ICU stay ≥24 hours and at least two blood glucose records within 24 hours after ICU admission were included and hospital mortality was chosen as the primary outcome. The average, minimum, and maximum blood glucose within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…Compared to other indicators, such as glycemic lability index 26 , 27 and mean amplitude of glycemic excursions 22 , 28 , Glucose_SD and Glucose_CV are simple, and their predictive values are similar; therefore, they are easier to use in clinical practice. In previous studies, glucose variability had a significant correlation with the mortality of ICU patients 29 31 , which concurs with our findings. In addition, we also used the Lowess smoothing curve to show the overall trend of the association between glucose variability and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 94%
“…Compared to other indicators, such as glycemic lability index 26 , 27 and mean amplitude of glycemic excursions 22 , 28 , Glucose_SD and Glucose_CV are simple, and their predictive values are similar; therefore, they are easier to use in clinical practice. In previous studies, glucose variability had a significant correlation with the mortality of ICU patients 29 31 , which concurs with our findings. In addition, we also used the Lowess smoothing curve to show the overall trend of the association between glucose variability and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 94%
“…The findings of this study are clinically relevant. Hyperglycemia is a common occurrence in the intensive care unit (ICU), is associated with worse outcomes in both adults and children, in both diabetics and non-diabetics, and an independent predictor of in hospital mortality in critically ill patients 12 14 , 46 , 47 . Further, acute increase in glycemia is accompanied by a large surge of inflammatory mediators, which worsens severity of disease 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Such spikes promote accelerated development of atherosclerosis leading to coronary artery disease, stroke, peripheral arterial disease and other vascular pathologies 9 11 . Additionally, hyperglycemia is an independent predictor of death in many acute settings, including acute myocardial infarction, trauma, head injury, stroke and has been shown to occur in the critical care setting in as many as 68% of the patients 12 14 . Therefore, interventions to prevent or minimize these fluctuations should be highly beneficial to health.…”
Section: Introductionmentioning
confidence: 99%
“… Li et al . (2020) [ 27 ] Retrospective Blood glucose within 24 h after ICU admission Average, minimum, and maximum blood glucose levels within 24 h of hospital admission Predicted lowest mortality risk and better prognosis for average and maximin blood glucose in the range of 110-140 mg/dL and for minimum blood glucose in the range of 80-110mg/dL within 24 hr after ICU admission 3. Mcgrade et al.…”
Section: Methodsmentioning
confidence: 99%
“…Association between blood glucose within 24 h after ICU admission and prognosis was evaluated in a retrospective cohort study in non-diabetic Chinese patients (n, 14,237). The authors showed that after adjusted for confounders including age, sex, disease severity scores and comorbidities, an average blood glucose ranged 110–140 mg/dL, a minimum blood glucose ranged 80–110 mg/dL, and a maximum blood glucose ranged 110–140 mg/dL was associated with the lowest risk of hospital mortality and better prognosis in patients without diabetes [ 27 ]. Association between admission glucose levels and mortality outcome was robustly shown in a cohort of 4102 hospitalized non-diabetic Israeli patients with heart failure.…”
Section: Methodsmentioning
confidence: 99%